Thermo-Luminescent Dosimeter Badge: Knowledge, Attitudes, and Barriers among Healthcare Personnel- A Cross Sectional Survey - Awadallah, Sawsan; Harwn, Ahmed; Guzailan, Hasan; Khalid, Nagla; Ahmed, Albosairi; Hashlan, Mohammed; Fathelrahman, Samia; Mohamed, Jihan; Hamed, Fatima Hamadain; Elfaki, Nahid (Disease and Health Research: New Insights Vol. 8, 2024)
Objective: Healthcare personnel are thought to be at significant risk of suffering the negative effects of ionizing radiation due to their high exposure. The goal of the current survey was to assess levels of knowledge and attitude, as well as the barriers to using thermo-luminescent dosimeter (TLD) devices among healthcare personnel for estimating radiation exposure doses. Methodology: A structured questionnaire survey was utilized to conduct a cross-sectional study. Results: A sum of 93 subjects participated in the current survey, the bulk were technicians who constitute (46.2%), while 40.9% were radiology physicians and nurses constituted 4.6% of the sample. Across the entire spectrum, a low level of attitude toward adhering to radiation safety and protocols was noticed among nurses, followed by physicians, while a good level of attitude towards using TLD badge was observed among technicians. On the other hand, the high level of knowledge towards radiation safety and usage of TDL badge was reported among physicians, followed by technicians and a low level of knowledge was among nurses. Conclusion and Recommendation: The survey revealed that the majority of radiology department personnel had a low attitude towards radiation safety and the use of TLD badges, despite having excellent knowledge about them. This highlights the need for action, particularly in enforcing protective strategies and clear protocols, along with educational initiatives to improve adherence to safety practices.